SIKAP HIDUP BERBUDAYA TOKOH DALAM NOVEL PASUKAN MATAHARI KARYA GOL A GONG - Sofiarti, Liza; Nurizzati, Nurizzati; Nst., Bakhtaruddin (Jurnal Bahasa dan Sastra, 2018)
This study aims to describe the cultural attitude of the character in the Novel of the Sun Forces by Gol A Gong, from the point of view of life, responsibility, love, justice, persistence in facing suffering, and perception of beauty. This type of research is qualitative research. The method used is descriptive. The data in this research is the characterization element especially the cultured attitude in the novel Pasukan Matahari by Gol A Gong. Based on the research, it can be concluded that the cultural attitudes of the characters found in the novel are addressing several issues, among others: (a) the view of life, the character in the Sun Pasukan novel has a strong and clear view of life based on values; (b) responsibility, the character of this novel of the Sun Forces has a good responsibility; (c) the conception of love; (d) the principle of justice, the character in this novel explains the fairness of the family and the course of law; (e) perseverance in the face of suffering, the character in this novel undergoes some form of suffering. It is seen from the character who suffered physical and nonphysical suffering, suffering in the form of complaints, suffering to bear something unpleasant; (f) the perception of beauty, the attitude of the figure to the beauty is depicted on the beauty of the creation of god.Â Keywords: Lifestyle, Culture, Novel